JIHAD IN THE BOOK OF TAFSIR AL-MUNIR WORK AG. H. DAUD ISMAIL - Hasmulyadi, Hasmulyadi (Journal of Islam and Science, 2018)
Jihad is mentioned in the al-Qur'an which is found in several surahs. Term jihad was repeated 41 times in various derivatives. Issue of jihad is one of the most sensitive issues and an interesting debate among scholars, Islamic intellectuals and Western intellectuals, both in the context of the doctrine of fiqh and social politics. Discussion of jihad raises the dynamics of pros and cons in understanding it, there are those who understand strictly so that jihad is understood as mere physical war. There are also those who understand it so loosely that it is understood that jihad is not necessary with physical war. This review discusses how to understand jihad according to AG.H. Daud Ismail is a Bugis charismatic scholar in his work Tafsir Al-Munir. This paper is a study of Tafsir al-Munir by K.H. Daud Ismail is the primary source. The meaning of jihad revealed by AG.H. Daud Ismail is a war and helps believers, be serious, defend the Qur'an and doing good. Jihad is divided into three, jihad against lust, jihad against Satan, and jihad against fellow human enemies.